1992
DOI: 10.1093/ptj/72.4.261
|View full text |Cite
|
Sign up to set email alerts
|

A Physical Therapy Model for the Treatment of Low Back Pain

Abstract: Low back pain is commonly seen in physical therapy practice, and many methods of treatment are used to reduce it. In this article, we discuss the magnitude of the low back pain problem, outline the various treatment methods, and develop a strategy to classify and standardize the treatment of the patient who has low back pain. We will develop this thought process by discussing five management considerations: (1) the dilemma of diagnosis, (2) the information gained from the assessment, (3) a patient classificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(21 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…2,3,7,8,[20][21][22]29,[31][32][33]40 Unfortunately, none of the systems has been tested extensively. The system of movement-related categories we have been testing was developed by Sahrmann,30 primarily on the basis of clinical observation.…”
mentioning
confidence: 99%
“…2,3,7,8,[20][21][22]29,[31][32][33]40 Unfortunately, none of the systems has been tested extensively. The system of movement-related categories we have been testing was developed by Sahrmann,30 primarily on the basis of clinical observation.…”
mentioning
confidence: 99%
“…While under the broad umbrella of manual therapy, Muscle Energy Technique (MET) does not fall into the subcategories of manipulation or mobilization. MET is an active technique 5,20 in that the patient, instead of the care provider, supplies the corrective force. 20 Greenman 20 defined MET as a ''manual medicine treatment procedure that involves the voluntary contraction of patient muscle in a precisely controlled direction, at varying levels of in- No other tensity, against a distinctly executed counterforce applied by the operator.''…”
mentioning
confidence: 99%
“…A report has indicated that more than 60% of men and women who work on the computer have complained of pain resulting from various MSIs (Idowu et al, 2005). Low back pain (LBP) is not only one of the most common MSIs in industrialized societies (Sanya and Ogwumike, 2005;Saidu et al, 2011), it is the most costly, and the primary cause of disability in persons under 45 years (DeRosa and Porterfield, 1992). In the United States, more than 25,000 ankle sprains occur each day and the concomitant symptoms (pains and swelling) leave the individuals with some functional disability (Man et al, 2007).…”
Section: Introductionmentioning
confidence: 99%